Time for learning : top 10 reasons why flipping the classroom can change education - Fulton, Kathleen (Thousand Oaks, California : Corwin, a SAGE Company, 2014)
This book provides a solid framework for talking about important aspects of educational change represented in classrooms that are being remodeled through flipping.
Why a book on flipped classrooms? -- How this book is different -- Who can benefit from this book? -- What is flipping anyway? -- How do teachers create flipped lessons? -- How different is flipping? -- The flipping mindset -- A brief history of flipping -- Lessons from higher education -- Blended learning and online content for K-12 -- Bergmann and Sams: flipping's early rock stars -- How common are flipped classrooms? -- Will flipping exacerbate the digital divide? -- Why is flipping catching fire? : read on!.
Includes bibliographical references (p. 155-162) and index.
Keywords: Blended learning; Homework -- Computer network resources